Woman with voice: an analysis of female agency in Dino Mudondo’s song,‘Jatirofa’and Josphat Somanje’s ‘Handibvume’ - Muwati, Itai; Tembo, Charles; Mutasa, Davie E. (Routledge, 2022)
The article is an exegesis of Shona songs which canonise the mother as a centrepiece of agency and family-centred commitments in times when family integrity comes under threat. Remarkably, the woman is privileged with a voice in a manner that thoroughly debunks stereotypical identities of the Shona/African woman as a personification of victimhood, non-participation, frailty and marginality as epitomised by Eurocentric feminist conceptualisations of women. The songs advance a lyrical agenda which contours musha (home) as a major performance space among the Shona people in which the man, woman and child are judged on the basis of their ability to contribute and participate responsibly. Within this spatial-cultural zone, the woman is cast as a significant life force, courageously vocalising her position in re-arranging, reshaping, challenging and re-ordering familial dynamics. The ownership of voice is critical in human affairs as it is coterminous with the enlargement of options and possibilities in life, something that remains indispensable to human growth and survival. As argued in the article, this participatory inclination by the mother together with the unbridled ownership of voice in the affairs of the family is consistent with Shona epistemological and ontological assumptions. For that reason, the discussion pivots on Africana Womanism, an African-centred paradigm on gender.